2006
DOI: 10.2337/diabetes.55.04.06.db05-1250
|View full text |Cite
|
Sign up to set email alerts
|

Combined Interleukin-6 and Interleukin-1 Deficiency Causes Obesity in Young Mice

Abstract: Proinflammatory cytokines including interleukin (IL)-1 and IL-6 exert pleiotropic effects on the neuro-immunoendocrine system. Previously, we showed that IL-1 receptor antagonist-deficient (IL-1Ra ؊/؊ ) mice show a lean phenotype due to an abnormal lipid metabolism. On the contrary, it was reported that IL-6 ؊/؊ mice exhibit obesity after 6 months of age. This study sought to assess the roles of IL-1 and IL-6 in body weight homeostasis. We generated mice deficient in IL-6 and IL-1Ra (IL-6 ؊/؊ IL-1Ra

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
65
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 44 publications
9
65
1
4
Order By: Relevance
“…We were unable to detect differences in food intake between the genotypes (data not shown). Overall, LT Ϫ/Ϫ mice did not show significant body weight or body fat gain over WT mice when fed a high-fat diet, and results are comparable with other mouse strains deficient in inflammatory mediators (8,46). Plasma total cholesterol levels were increased ϳ40% for HFHS-fed mice (120 mg/dl) compared with mice fed rodent chow (80 mg/dl), but no significant differences were seen between the genotypes.…”
Section: Lt Deficiency Results In Reduced Obesity Body Weights For Ltsupporting
confidence: 57%
See 1 more Smart Citation
“…We were unable to detect differences in food intake between the genotypes (data not shown). Overall, LT Ϫ/Ϫ mice did not show significant body weight or body fat gain over WT mice when fed a high-fat diet, and results are comparable with other mouse strains deficient in inflammatory mediators (8,46). Plasma total cholesterol levels were increased ϳ40% for HFHS-fed mice (120 mg/dl) compared with mice fed rodent chow (80 mg/dl), but no significant differences were seen between the genotypes.…”
Section: Lt Deficiency Results In Reduced Obesity Body Weights For Ltsupporting
confidence: 57%
“…To test the role of individual inflammatory proteins in obesity, genes have been ablated in mice and shown to induce obesity (8,16,39,46,54,55,68,73,86). Nearly all of these genes relate to monocyte tissue infiltration and/or macrophage activation and phenotypic switching.…”
mentioning
confidence: 99%
“…Considering the fact that Il1ra −/− mice on a HFD had increased body temperature, it is possible that the primary effect of Il1ra deficiency is to increase body temperature. However, we have previously demonstrated that Il1ra −/− Il-6 −/− mice on a normal diet show a lean phenotype comparable to Il1ra −/− mice [32]. Since IL-6 is essential for the IL-1-induced febrile response [37,38], it is not possible that the lean phenotype could be explained solely by the action of IL-1 as a pyrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, knockout of IL-RI, IL-6, and GM-CSF all result in mature-onset obesity, indicating that age-related cofactors are needed to obtain the obese phenotype (22,53). It has recently been reported that IL-1 receptor modulation also affects body fat in IL-6 knockout mice (54), but else there is little knowledge about the interactions between these three cytokines. Taken together, these results indicate interactions between several components of the immune system and body fat regulation.…”
Section: Discussionmentioning
confidence: 99%